Proteomic analyses of the regulatory mechanisms underlying Pochonia chlamydosporia infection in Parascaris equorum eggs - Ma, Yuan; Lv, Jinbao; Hao, Luyao; Li, Zhengyi; Ma, Chengyu; Wang, Rui; Jiang, Lili; Fan, Zhaobin (Frontiers in Microbiology, 2025)
BackgroundPochonia chlamydosporia is an important egg-parasitic fungus with potential applications in the biological control of parasitic pests. However, the protein-response mechanisms during P. chlamydosporia infection of nematode eggs remain unclear. In this study, we employed four-dimensional data-independent acquisition (4D-DIA) proteomic sequencing to analyze the changes in the mycelial proteome of P. chlamydosporia at different infection stages.ResultsIn total, 4,293 differentially expressed proteins (DEPs) were identified, which were mainly involved in energy metabolism, protein synthesis and modification, oxidative stress, and other key biological processes. In the early stages of infestation, the fungus rapidly adapted to the host environment by enhancing metabolism and protein synthesis, initiating the infestation mechanism, and simultaneously enhancing its antioxidant capacity to cope with the host defense response. At later stages, it fine-tuned the metabolic pathways and enhanced DNA replication to maintain proliferation and continuously strengthened the antioxidant response to host oxidative stress. In addition, the number of proteins related to fungal transporter activity varied significantly after induction, indicating that a variety of transmembrane proteins may be involved in host recognition, adhesion, and formation of invasive structures.ConclusionThis study provides critical insights into the molecular mechanisms underlying P. chlamydosporia parasitic activity and establishes a theoretical foundation for the development of novel biocontrol strategies for this fungus.